Integrating Tubb’s Engagement Model with Critical Reading - Ibrahim, Irma Wahyuny; Rahmat, Noor Hanim; Shahabani, Nor Syahiza; Nasharudin, Sharifah Nadia Syed; Ghazali, Izlin Mohamad; Khairuddin, Zulaikha (International Journal of Asian Social Science, 2021)
Since critical reading has been assumed as critical, there are actually certain ideas and concepts that reflect how critical is this critical reading. Critical does not mean critical as in difficulty or failure in reading but more of looking into the skills, processes and the activities when reading. Group engagement has been said to improve team members’ critical thinking skills. This study is done to explore how group interactions facilitate critical reading activities. Specifically, this study explores how group work encourages critical reading through the processes of orientation, conflict, consensus, and closure. 72 participants responded to the instrument (a questionnaire). The questionnaire has 5 sections, demographic profile, orientation, conflict, consensus and also closure. Data is analyzed using SPSS version 26 to reveal percentage for the demographic profile and mean score for the variables. Findings indicate that group engagement facilitates critical reading in several ways. The study suggests that communication during group interaction improves learners’ critical reading.